Vegetable and Fruit Intakes of On-Reserve First Nations Schoolchildren Compared to Canadian Averages and Current Recommendations - Gates, Allison; Hanning, Rhona M.; Gates, Michelle; Skinner, Kelly; Martin, Ian D.; Tsuji, Leonard J. S. (International Journal of Environmental Research and Public Health, 2012)
This study investigated, in on-reserve First Nations (FN) youth in Ontario, Canada, the following: (a) the intakes of vegetable and fruit, “other” foods and relevant nutrients as compared to current recommendations and national averages, (b) current prevalence rates of overweight and obesity and (c) the relationship between latitude and dietary intakes. Twenty-four-hour diet recalls were collected via the Waterloo Web-Based Eating Behaviour Questionnaire (WEB-Q) (n = 443). Heights and weights of participants were self reported using measured values and Body Mass Index was categorized using the International Obesity Task Force cutoffs. Food group and nutrient intakes were compared to current standards, Southern Ontario Food Behaviour data and the Canadian Community Health Survey, Cycle 2.2, using descriptive statistics. Mean vegetable and fruit, fibre and folate intakes were less than current recommendations. Girls aged 14–18 years had mean intakes of vitamin A below current recommendations for this sub-group; for all sub-groups, mean intakes of vegetables and fruit were below Canadian averages. All sub-groups also had intakes of all nutrients and food groups investigated that were less than those observed in non-FN youth from Southern Ontario, with the exception of “other” foods in boys 12–18 years. Prevalence rates of overweight and obesity were 31.8% and 19.6%, respectively, exceeding rates in the general population. Dietary intakes did not vary consistently by latitude (n = 248), as revealed by ANOVA. This study provided a unique investigation of the dietary intakes of on-reserve FN youth in Ontario and revealed poor intakes of vegetables and fruit and related nutrients and high intakes of “other” foods. Prevalence rates of overweight and obesity exceed those of the general population.